Third Party Liability Insurance for Space Activities: International Law Aspects - G. P. Zhukov; O. A. Volynskaya (Московский журнал международного права, 2012)
The development of space activities provides for economic growth, scientific, technical and social development, strengthening of the defensive power. A developed insurance system protects space operators against financial consequences of a possible damage.States are obliged to compensate any damage to third parties caused by national space activities under the 1967 Outer Space Treaty and the 1972 Liability Convention. To ensure performance of the obligation specific insurance mechanisms were implemented in national space laws. This article analyses regulatory insurance regimes and provides an insight into the current state and perspectives of Russian space law covering third party liability insurance.